Novel candidates for chronic diabetic wound healing - Khan, Muhammad Shakil; Tauqeer Ahmed Malik (Journal of Pakistan Association of Dermatologists, 2022)
Diabetic Foot Ulcer (DFU) is a leading cause of amputation in adult population all over the world. Molecular pathology of delay in wound healing of diabetic foot ulcer patient is not completely understood till today. Numerous works has been required to explore the cause of delay in wound healing which ultimately end in amputation. To find the role of long non-coding RNAs is a promising strategy which could be beneficial in treating the chronic wound timely and progressively. We have selected long non-coding RNAs (ANRIL and its target miR-181a, H19 and its target miR-29b) which are involved in the inflammation, proliferation and remodeling phase of wound healing process and do comparison of their expression in DFU patients and normal healthy individuals. Our results revealed that ANRIL down regulation and H19 up regulation in DFU patients and similarly miR-181a up regulation and miR-29b down regulation. These results needed further validation by sequencing work therefore these can be used as diagnostic marker for an early detection in diabetic patients to halt the progression of DFU wound healing delay. Keywords: Diabetic Foot Ulcer; amputation; long non-coding RNAs